The Value of Islamic Education in the Sedekah Bumi ritual - Hariman Surya Siregar; Miftahul Fikri; Ririn Khorinnisa (AL-ISHLAH: Jurnal Pendidikan, 2021)
This research is motivated by the existence of a culture about the annual ritual of sedekah bumi which is always carried out by the community. The purpose of this study was to find out the values of Islamic education contained in the sedekah bumi tradition. The research method used is descriptive qualitative using data collection techniques in the form of interviews, observations, documentation and literature studies. The results of the research show that in the sedekah bumi tradition there are values of Islamic education in the form of values of faith, brotherhood and togetherness, mutual help, friendship, sharing benefits by doing prayer together and thanksgiving. The implication of this research is that the community can review the various positive sides of the earth alms tradition because not all things related to tradition and culture contain elements of shirk and make traditions that are always carried out as content containing the value of Islamic education.